Efeitos da N-acetilcisteína sobre o dano oxidativo renal e hepático de ratos diabéticos - Ribeiro, Gianine Lima (2010)
Diabetes mellitus (DM) is a chronic disease characterized by hyperglycemia, which is related to oxidative stress and plays an important role in the development of other diseases and tissue damage, such as liver and kidney damage. Thus, it is important for studies with potential antioxidant that may reduce the deleterious effects of oxidative stress due to diabetes. In this sense, N-acetylcysteine (NAC) is used as a hepatoprotective drug in the treatment of acute poisoning by paracetamol to reduce oxidative damage. Along these lines, the aims of this study were to evaluate biomarkers of oxidative stress such as reduced glutathione (GSH), glutathione peroxidase (GPx), superoxide dismutase (SOD), malondialdehyde (MDA) and delta aminolevulinate acid dehydratase (ALA-D) in liver and kidneys of controls and animals with diabetes induced after treatment with NAC. Treatments consisted of intraperitoneal administration of 25 mg / kg and 75 mg / kg N-acetylcysteine. In the liver, MDA levels were significantly increased in the diabetic group compared to controls, treatment with 75 mg / kg reduced the levels of MDA, being similar to the control group. GSH levels of the enzyme was found to be highest in kidney and liver of diabetic animals than controls, and treatment with NAC led to these reduced levels in the liver of diabetic animals, but in the kidney, no changes. The levels of SOD and GPx decreased in the liver of diabetic animals compared to control, and administration of NAC did not alter these indices. Diabetes also reduced the activity of ALA-D in the liver, and treatment with 25 mg/ kg NAC did with this activity increased significantly. In the kidney, both doses of NAC increased the levels of ALA-D in diabetic animals. The results suggest that NAC may be more effective in the liver, the organ that suffers most oxidative changes, and especially in groups of diabetic animals.